Gamma Radiolysis of TODGA and CyMe4BTPhen in the Ionic Liquid Tri-n-Octylmethylammonium Nitrate. Issue 2 (23rd February 2020) - Zsabka, Peter; Van Hecke, Karen; Wilden, Andreas; Modolo, Giuseppe; Hupert, Michelle; Jespers, Vincent; Voorspoels, Stefan; Verwerft, Marc; Binnemans, Koen; Cardinaels, Thomas
ABSTRACT: Radiolytic stability of the extractants N, N, N', N' -tetraoctyl diglycolamide (TODGA) and 2, 9-bis(5, 5, 8, 8-tetramethyl-5, 6, 7, 8-tetrahydro-1, 2, 4-benzotriazin-3-yl)-1, 10-phenanthroline (CyMe4 BTPhen) in the ionic liquid tri- n -octylmethylammonium nitrate ([N1888 ][NO3 ]) was studied via the combination of a steady-state irradiation by cobalt-60 gamma-radiation, followed by solvent extraction and identification of radiolysis products by High-Performance Liquid Chromatography coupled to Electro Spray Ionisation Mass Spectrometry (HPLC-ESI-MS). The observed trend for the distribution ratios of trivalent minor actinides and Eu(III) showed a decrease as a function of absorbed dose in the case of the TODGA solvent. The gamma irradiations were conducted in the presence or absence of an acidic aqueous phase. The determined dose constants for TODGA under neutral or acidic conditions were up to four times lower than the values reported in aliphatic diluents under comparable conditions. The degradation patterns were similar to those found by former studies on TODGA diluted in n -dodecane; only de-alkylation and bond ruptures within the diglycolamide core were observed. The presence of an acidic aqueous phase during irradiation resulted in a different relative abundance of certain radiolysis products of both the diluent and TODGA and a higher dose constant compared to the neutral irradiation conditions. A quantification of CyMe4 BTPhen in irradiated samples with the [N1888 ][NO3 ] diluent was not possible, but the effect on its extraction properties was evaluated. The distribution ratios slightly increased under the effect of absorbed dose, indicating the formation of radiolysis products that are efficient extractants as well.